2021
DOI: 10.4103/jfmpc.jfmpc_2301_20
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Child Restraint System Use and Pattern of Child Transportation in Buraidah City

Abstract: Background: The motor vehicle crash (MVC) is a major cause of injuries and deaths among children worldwide. The child restraint system (CRS) is designed to protect children from injury and death if passengers are involved in MVC. Objectives: To determine the prevalence of CRS use for children aged 5 years and below and to explore the pattern of child transportation inside cars in Buraidah, Saudi Arabia. Methods: A cross-sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Our findings are in line with the local study conducted in Unaizah, which found gender (p<0.001), educational level (p=0.004), and the number of children (p=0.009) to be significantly associated with attitude [ 24 ]. Other reports from Saudi Arabia showed similar findings [ 21 - 23 ]. Such results align with the need to address gender-specific concerns or misconceptions about CSS use.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are in line with the local study conducted in Unaizah, which found gender (p<0.001), educational level (p=0.004), and the number of children (p=0.009) to be significantly associated with attitude [ 24 ]. Other reports from Saudi Arabia showed similar findings [ 21 - 23 ]. Such results align with the need to address gender-specific concerns or misconceptions about CSS use.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, a cross-sectional study of 350 parents from Unaizah City in Saudi Arabia showed low knowledge and an unfavorable attitude toward CSS use [ 18 ]. Another report showed that parents from Buraidah, Saudi Arabia, had a low level of utilization of CSS, and most respondents were unaware of CSS's importance and regulations in Saudi Arabia [ 21 ]. A more recent report from Jeddah, Saudi Arabia, recruited 192 mothers to assess their knowledge and practice of CSS.…”
Section: Discussionmentioning
confidence: 99%
“…The first is PSE1 ("In case of a crash where a child/children is/are not in a child restraint system, it may affect their education"), with a coefficient of 0.599, which is logical because an accident may cause severe injury or disability to a child and have long-term effects on their education and daily life, both emotionally and physically. This finding indicates that increasing parents' awareness of these issues will also likely increase their willingness to use a CRS [75].…”
Section: Structural Modelsmentioning
confidence: 88%
“…[ 12 ] A recent study from Buraidah city found that 40.9% of respondents had CSS available in their vehicles, and only 15.5% used it at all times while driving. [ 13 ] Lastly, a cross-sectional study conducted at Jeddah’s well-baby clinics at primary healthcare centers in 2020 reported that 37.5% of participants had a CSS, and only 18.2% used it regularly. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%